E-Commerce & Direct Selling: A Big Solution for Underemployment & Unemployment - Kumar, Rakesh (Digital Repository of Theses, 2025)
This study looks at how e-commerce and direct selling can help young people in India who are unemployed or underemployed. Unemployment (not having a job at all) is still a big problem, but underemployment (having a job that is below your skill level or capacity) is even worse and has a bigger impact on youth development. The Periodic Labour Force Survey (PLFS) says that India's youth unemployment rate fell to 10.2% in 2023–24. At the same time, the percentage of people in the labour force rose from 31.4% in 2017–18 to 41.7% in 2023–24 (PIB, 2024). This shows that more people are getting involved, but not necessarily using their skills to their full potential. At the same time, almost 83% of India's unemployed people are between the ages of 15 and 29. Many of them are educated but working in jobs that don't match their skills. As a result, gig economy platforms, digital product sales, and affiliate marketing have become flexible and scalable options. Amway India's switch to digital tools changed their e-commerce share from about 33% in early 2020 to about 70% in 2021 (Nischala, 2024). This shows how digital direct selling can greatly increase reach and income opportunities. Amazon's affiliate program also lets people make money from online content without having to spend a lot of money. Some young creators have been able to make a lot of money through this program, with commissions ranging from 1% to 10% depending on the type of product. These models have low barriers to entry, independence, and the ability to grow, which are all things that young people who don't want to do traditional "white-collar" or low-paying jobs want. This change helps people grow mentally, spiritually, and personally, in addition to financially. Working as a gig worker, micro-entrepreneur, or digital seller improves self-efficacy, problem-solving skills, and a sense of ownership. These roles give people a sense of purpose and connection to online communities, which boosts their self-esteem, which is especially important for young people who aren't using their time well. Even a small amount of income can help people stay financially stable and lower their stress levels, which lets them focus on growth, stability, and self-improvement. In the end, the study says that e-commerce-driven direct selling and gig work can help solve the problem of underutilised labour if they are supported by policies, digital infrastructure, and programs that help people learn new skills. These models don't solve all problems, but they do help traditional job paths by giving young people with skills and education a place to work that is dignified, flexible, and allows for growth. The study suggests that India should use this chance by combining digital entrepreneurship with targeted training and rules. This kind of plan could help millions of young people who are not working enough become engaged, empowered contributors to economic growth and social well-being.